Assessment of knowledge regarding the consequences of using earphones among higher secondary and non-medical postgraduate students - Das, Jiban Jyoti (International Journal Of Community Medicine And Public Health, 2020)
Background: Due to the incremental scope of using earphones, in today’s world youngsters are susceptible to loud sounds or prolong sounds that may cause negative consequences to them in the later run. Aim of the study was to assess the knowledge regarding the consequences of the use of earphones in terms of basic level and advanced levels of awareness among some high secondary students and non-medical postgraduate students. Methods: A structure questionnaire-based study was done by distributing it among the students of Pondicherry central university, Puducherry, India, and Delhi Public School, Digboi Assam. 18 students from different departments of the Pondicherry central university and 19 students from the high secondary of Delhi Public School, Digboi were selected randomly for the study. A structured questionnaire consisting of questions related to the consequences of using earphones was used as a study tool for observation. Sets of questions related to the awareness were categorized into basic level, advanced level-1, and advanced level-2. Results: Knowledge scores for basic level awareness showed very good results. Knowledge scores for advanced level 1 and 2 awareness showed poor results for both the groups. Conclusions: The study highlights the requirement of developing awareness programs regarding health hazards associated with the use of earphones in terms of parameters like the feeling of ringing like sounds through the ears, ear wax, ear stress, ear pain, and tinnitus. Such awareness needs to be incorporated in textbooks of the school level.